Prosta-omics: machine learning-driven TPSA prediction and molecular modeling of ASPM-inhibitors for prostate cancer treatment - Kashif Iqbal Sahibzada; Shumaila Shahid; Saba Shahid; Andleeb Batool; Yuansen Hu; Dong-Qing Wei (Molecular Diversity, 2026)

Leucocoprinus aurantiopileus (Agaricaceae), a New Species from Pakistan - Fazli Maula; Malka Saba; Muhammad Asif; Afifa Kainat Rani; Wajahat Akram; Fahim Ullah; Saher Batool; Kainat Bakhsh; Ayesha Bibi; Aiman Izhar; Najam Ul Sehar Afshan; Abdul Nasir Khalid (New Zealand Journal of Botany, 2026)
A novel species, Leucocoprinus aurantiopileus , is described from Margalla Hills National Park, Islamabad, Pakistan, using an integrated approach. Phylogenetic analyses based on combined internal transcribed spacer and large subunit sequences confirm its placement within Leucocoprinus . L. aurantiopileus is distinguished by a conical to campanulate, subumbonate to umbonate pileus, dark red center, and light orange margins, along with subcylindrical to oblong basidiospores. We provide detailed descriptions, colored photographs, microscopic structures, and a phylogenetic tree. This discovery highlights the mycological diversity of Margalla Hills and emphasizes the need for further fungal exploration in the region.

Innovative Nanotechnology and Molecular Probes for Real-time Monitoring and Therapeutic Modulation of Pyroptosis in Cancer and Inflammatory Diseases - Wajahat Ali; Zainab Saba; Muhammad Saqib; Shabana Batool; Awais; Fatima Rahman; Ali Asgher Shuja; Junaid Abid; Seema Batool; Kulsoom; Mukhayya Ruzieva; Murodjon Yaxshimuratov; et al. (Cell Biochemistry and Biophysics, 2025)

Enhanced catalytic stability for L-Dopa synthesis through cross-linking of Al₂O₃ nanocrystals with Bacillus subtilis tyrosine hydroxylase - Areesha Batool; Sikander Ali; Aneeba Rashid; Muhammad Usman Ahmad; Saba Sana; Luiza C. Campos (World Journal of Microbiology and Biotechnology, 2025)
This study focuses on enhancing L-Dopa synthesis by producing tyrosine hydroxylase from Bacillus subtilis SDSC-Env-i6 and its conjugation with aluminium oxide (Al₂O₃) nanoparticles. The free enzyme exhibited moderate activity, which was significantly improved through nanoparticle conjugation. Structural characterisation confirmed successful binding, with Al₂O₃ nanoparticles showing a crystalline nature and sizes ranging from 124 to 130 nm. Compared to the free enzyme, the Al₂O₃-conjugated tyrosine hydroxylase demonstrated markedly enhanced catalytic activity, reaching up to 15.3 ± 0.05 U/mL under optimised conditions. In contrast, maximum activities for the free enzyme were 5.5 ± 0.05 U/mL and 6.3 ± 0.11 U/mL in the presence of CuCl₂ and CaCl₂, respectively. The cross-linked enzyme also showed superior stability and efficiency across varying conditions. L-Dopa production was significantly higher with the conjugated enzyme, yielding between 0.531 and 1.105 mg/mL under optimised incubation conditions. These values were notably greater than those achieved using the free enzyme across different pH levels, volumes, and incubation times. Spectroscopic and microscopic analyses confirmed the integrity and functionality of the enzyme-nanoparticle complex. The observed improvements in both enzyme activity and L-Dopa yield were statistically significant ( p ≤ 0.05), underscoring the potential of Al₂O₃ nanoparticle-conjugated tyrosine hydroxylase as an efficient and scalable biocatalyst for commercial L-Dopa production. Determination of kinetic parameters showed maximum V max /K m (1.25 × 10 6 ) was observed when immobilized tyrosinase activity was characterized with tyrosine as substrate, with significant K cat value of 1.48 × 10 18 s − 1 .

Integrative taxonomy and multigene phylogeny uncover three novel taxa of the genus Clitopilus from southern Punjab, Pakistan - Muhammad Asif; Malka Saba; Wajahat Akram; Fazli Maula; Fahim Ullah; Momal Batool; Mohsin Ullah; Irmgard Krisai-Greilhuber; Mubashar Raza (Mycological Progress, 2025)

Effective synergism of Moringa oleifera with antibiotics, body growth, and decoction replacement - Qandeel Ashraf; Amjad Islam Aqib; Hamid Majeed; Shahbaz Ul Haq; Muhammad Farrukh Nisar; Muhammad Usman; Afshan Muneer; Saba Batool; Farid S. Ataya (South African Journal of Botany, 2024)

A New Hybrid Weighted Regional Drought Index to Improve Regional Drought Assessment - Alina Mukhtar; Aamina Batool; Zulfiqar Ali; Sadia Qamar; Saba Riaz; Saad Sh. Sammen (Water Resources Management, 2024)

Nano-based remediation strategies for micro and nanoplastic pollution - Nayab Batool Rizvi; Adnan Sarwar; Saba Waheed; Zeenat Fatima Iqbal; Muhammad Imran; Ayesha Javaid; Tak H. Kim; Muhammad Shahzeb Khan (Journal of Contaminant Hydrology, 2024)

Analysis of Putative Epitope Candidates of Mycobacterium tuberculosis Against Pakistani Human Leukocyte Antigen Background: An Immunoinformatic Study for the Development of Future Vaccine - Malik Siddique Mahmood; Duaa Bin-T-Abid; Saba Irshad; Hina Batool (International Journal of Peptide Research and Therapeutics, 2021)

Plant growth promoting rhizobacteria in sustainable agriculture: from theoretical to pragmatic approach - Samar Mustafa; Saba Kabir; Umbreen Shabbir; Rida Batool (Symbiosis, 2019)